The Role of Prospection in Steep Temporal Reward Discounting in Gambling Addiction - Wiehler, Antonius; Bromberg, Uli; Peters, Jan (Frontiers in Psychiatry, 2015)
Addiction and pathological gambling (PG) have been consistently associated with high impulsivity and a steep devaluation of delayed rewards, a process that is known as temporal discounting (TD). Recent studies indicated that enhanced episodic future thinking (EFT) results in less impulsive TD in healthy controls (HC). In a separate line of research, it has been suggested that non-linearities in time perception might contribute to reward devaluation during inter-temporal choice. Therefore, in addition to deficits in valuation processes and executive control, impairments in EFT and non-linearities in time perception have been hypothesized to contribute to steep TD in addiction. In this study, we explore such a potential association of impairments in EFT and time perception with steep TD in PG. We investigated 20 PGs and 20 matched HCs. TD was assessed via a standard computerized binary choice task. We measured EFT using a variation of the Autobiographical Memory Interview by Levine et al. (1). Time perception was assessed with a novel task, utilizing a non-linear rating procedure via circle-size adjustments. Groups did not differ in baseline EFT. In both groups, a power law accounted time perception best, and the degree of non-linearity in time perception correlated with discounting across groups. A multiple regression analysis across all predictors and covariates revealed that only group status (PG/HC) and depression were significantly associated with discounting behavior such that PG increased TD and depression attenuated TD. Our findings speak against the idea that steep TD in PG is due to a skewed perception of time or impairments in EFT, at least under the present task conditions. The lack of overall group differences in EFT does not rule out the possibility of more complex interactions of EFT and decision-making. These interactions might be diminished in pathological gambling or addiction more generally, when other task configurations are used.